2013
DOI: 10.1186/1471-2393-13-57
|View full text |Cite
|
Sign up to set email alerts
|

Sexual HIV risk behaviour and associated factors among pregnant women in Mpumalanga, South Africa

Abstract: BackgroundThe HIV risk increases during pregnancy. The elevated risk of HIV acquisition in pregnant women may be explained by behavioural and other factors. The aim of this study was to assess sexual HIV risk behaviour and its associated factors among pregnant women in Mpumalanga, South Africa.MethodsA cross-sectional study was conducted among 1 502 pregnant women (age range 18–47 years, mean age 26.6 years, standard deviation (SD) 6.1, and the mean gestational age was 6.5 months (SD 1.6). Antenatal women were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 34 publications
2
27
0
Order By: Relevance
“…However, our observation was very high relative to statistics from other African countries such as Uganda,29 Kenya,30 Malawi,31 Zambia,32 and Nigeria 33. A study in Mpumalanga, South Africa among pregnant women found that the prevalence of MSP was 20% 34. These variations suggest that the magnitude of MSP depends on the context at hand because populations differ in several aspects including locations, cultures, values, beliefs, norms, and practices.…”
Section: Discussionmentioning
confidence: 99%
“…However, our observation was very high relative to statistics from other African countries such as Uganda,29 Kenya,30 Malawi,31 Zambia,32 and Nigeria 33. A study in Mpumalanga, South Africa among pregnant women found that the prevalence of MSP was 20% 34. These variations suggest that the magnitude of MSP depends on the context at hand because populations differ in several aspects including locations, cultures, values, beliefs, norms, and practices.…”
Section: Discussionmentioning
confidence: 99%
“…There are biological and behavioural factors that drive high HIV incidence during pregnancy and breastfeeding periods such as hormonal changes that alter genital mucosal surfaces, and frequent condomless sex with HIV-infected partners or partners of unknown serostatus [3, 69]. Maternal seroconversion during pregnancy and breastfeeding contributes significantly toward paediatric HIV infections in sub-Saharan Africa [3, 10].…”
Section: Introductionmentioning
confidence: 99%
“…1115 The risk of individual infection showed in a multivariate model that pregnancy was associated with higher risk of chlamydia, VVC, and any STI or RTI.…”
Section: Discussionmentioning
confidence: 99%